Penerapan Metode Klasifikasi ABC pada Penyimpanan Gudang Suku Cadang PT. Pupuk Kujang Cikampek - Putra, Dewa Pratama; Tobing, Doni Ronaldo Lumban; Winarsih, Neneng (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
Warehouse is a place for storing company's goods. Activities in the warehouse include inventory and goods management. PT. Pupuk Kujang Cikampek faces difficulties in this regard. This is due to the manual inventory process, which takes a long time to retrieve information about the goods. Therefore, the aim of this research is to implement the ABC classification method in the spare parts warehouse of PT. Pupuk Kujang Cikampek to simplify the inventory and goods management process. The ABC classification method is used to group items into certain classes based on their annual demand. This method is used to organize the placement of goods in the warehouse. After implementing the ABC method in the system, the company finds it helpful in preparing and placing goods and knowing the most needed goods information by consumers. The result of this research is Category A referred to as fast-moving items, with a total of 15 items. Category B is referred to as medium-moving items, with a total of 8 items. Category C is referred to as slow-moving items, with a total of 66 items. From the data processing results, Category C is more than Categories A and B. Therefore, organizing goods using the ABC classification method will affect the warehouse layout in the spare parts warehouse. Keywords: ABC Classification, Grouping, Warehouse